Community-based interventions against HIV-related stigma: a systematic review of evidence in Sub-Saharan Africa - Emmanuel Kimera; Linda Grace Alanyo; Irumba Pauline; Maureen Andinda; Enos Masereka Mirembe (Systematic Reviews)
Abstract Background HIV-related stigma remains a key barrier to the attainment of the UNAIDS global goal of ending AIDS by 2030. Due to the social and contextual nature of HIV-related stigma, community-based interventions may be more effective in addressing it. In this review, we synthesized evidence on the effectiveness and features of community-based interventions against HIV-related stigma in Sub-Saharan Africa. Methods MEDLINE, EMBASE, CINAHL, Psych INFO, and Web of Science were searched in July 2023. We also searched Google Scholar and reference lists of all selected studies. Included studies were randomized controlled trials, mixed methods studies, as well as pre-test and post-test studies that evaluated the effectiveness of a community-based intervention to reduce HIV-related stigma in the general population or among specific groups. Data extraction was done using a pre-designed and pre-tested form. We performed a synthesis without meta-analysis, utilizing Fisher’s method to combine p-values, to demonstrate evidence of an effect in at least one study. Additionally, we applied framework thematic analysis to qualitatively synthesize the intervention characteristics of the included studies. Results A total of nine journal articles were included, largely with a high risk of bias. Results from the combined p-values provide strong evidence supporting the effectiveness of community-based interventions in reducing HIV-related stigma in at least one of the studies (p < 0.001, X 2 = 73.1, 18 degrees of freedom). Most studies involved people living with HIV (PLH) alone as intervention recipients and as intervention implementers. Community members with unknown HIV status were involved in only 2 studies. The intervention strategies were largely information sharing through workshops and training as well as individualized counselling. In few studies, additional support in the form of referrals, nutritional supplements, and adherence support was provided to PLH during the interventions. Most studies were judged to be of moderate to high cost except in 3 where the intervention implementers were PLH within the community, volunteering in the home-based support approach. The involvement of community members in the design of intervention strategies was not seen in all the studies. Conclusion Community-based interventions appear to be effective in reducing HIV-related stigma. However, more robust randomized trials are needed to provide stronger evidence for this effect. Although these interventions have been multifariously developed in Sub-Saharan Africa, comprehensive strategies involving the stigmatized and the “stigmatizers” in a social change approach are lacking. The application of strategies without the involvement of community members in their design takes away a sense of community responsibility, and this threatens the sustainability of such interventions. Systematic review registration PROSPERO CRD42023418818.